Optically Powered Highly Energy-efficient Sensor Networks - Röger, Moritz (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2013)
In optically powered networks, both, communication signals and power for remotely located sensor nodes, are transmitted over an optical fiber. Key features of optically powered networks are node operation without local power supplies or batteries as well as operation with negligible susceptibility to electro-magnetic interference and to lightning. In this book, different kinds of optically powered devices and networks are investigated, and selected applications are demonstrated.